Granulocytes: New Members of the Antigen-Presenting Cell Family - Lin, Ang; Loré, Karin (Frontiers in Immunology, 2017)
Granulocytes, the most abundant types of leukocytes, are the first line of defense against pathogen invasion. However, the plasticity and diversity of granulocytes have been increasingly revealed, especially with regards to their versatile functions in orchestrating adaptive immune responses. A substantial body of recent evidence demonstrates that granulocytes can acquire the function as antigen-presenting cells (APC) under pathological or inflammatory conditions. In addition, they can acquire surface expression of MHC class II and co-stimulatory molecules as well as T cell stimulatory behavior when cultured with selected cytokines. The classic view of granulocytes as terminally differentiated, short-lived phagocytes, is therefore changing to phenotypically and functionally heterogeneous cells that are engaged in cross-talk with other leucocyte populations and provide an additional link between innate and adaptive immunity. In this brief review, we summarize the current knowledge on the antigen-presenting capacity of granulocyte subsets (neutrophils, eosinophils, basophils). Underlying mechanisms, relevant physiological significance and potential controversies are also discussed.